2015
DOI: 10.1007/s00784-015-1499-z
|View full text |Cite
|
Sign up to set email alerts
|

Non-surgical periodontal therapy supplemented with systemically administered azithromycin: a systematic review of RCTs

Abstract: When contraindications for the standard antibiotics are present, azithromycin (AZM) may be considered as alternative systemically administered antibiotic drug in selected cases of chronic periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 69 publications
(185 reference statements)
1
12
1
1
Order By: Relevance
“…Regarding the healing time post NSPT, the evidence indicates a marked reduction of PPD after three months. However, in the initial deep sites, wound healing seems to need more time [21]. The reduction in PPD obtained in the AZM group in this investigation coincides with these healing times (Fig.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Regarding the healing time post NSPT, the evidence indicates a marked reduction of PPD after three months. However, in the initial deep sites, wound healing seems to need more time [21]. The reduction in PPD obtained in the AZM group in this investigation coincides with these healing times (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…These results differ from those described in previous studies, where no signi cant differences between study groups were observed at any time points [13,18,19]. Otherwise, previous research [20,21] reported a signi cant reduction in the average PPD, consistent with this study. From baseline to the third month post NSPT, a signi cant increase in the mean number of sites with PPD 1-3 mm was observed in the test group (Fig.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…However, the authors warned of some risk of bias in some of the studies. Furthermore, there was no evidence of superiority of Az over A+M …”
Section: Discussionmentioning
confidence: 94%
“…y col. 13 en el 2015, encontraron mediante una revisión sistemática un beneficio potencial de la administración sistémica de azitromicina como adyuvante a la terapia periodontal no quirúrgica en pacientes con periodontitis crónica.…”
Section: Introductionunclassified